Chronological and environmental context of the first hominin dispersal into Western Europe: The case of Barranco León (Guadix-Baza Basin, SE Spain). Issue 87 (October 2015) - Agustí, Jordi; Blain, Hugues-Alexandre; Lozano-Fernández, Iván; Piñero, Pedro; Oms, Oriol; Furió, Marc; Blanco, Angel; López-García, Juan Manuel; Sala, Robert
Abstract: The early Pleistocene site of Barranco León (Guadix-Baza Basin, SE Spain), dated to 1.4 Ma (millions of years ago), records the oldest hominin occurrence in Western Europe, as evidenced by the discovery of one tooth and thousands of Mode 1 stone tools. In this paper a detailed analysis of the microvertebrate content of the D1 and D2 units from this site is presented. The early Pleistocene in the Guadix-Baza Basin is characterized by a sharp climatic deterioration, which possibly impeded the settlement of this region by the early hominin population from the southern Caucasus. Shortly afterwards, when the climatic conditions were again favorable, a hominin presence is suddenly evidenced at the units D1 and D2 of Barranco León. According to the microvertebrate analysis of these units, the mean annual temperature at the time of deposition was significantly higher than 13 °C, with prevalent humid conditions. However, although most of the species were inhabitants of water edges, an open landscape was present in the vicinity of the lake. The data reported here clearly support the idea that the early hominin occupation of Europe was strongly constrained by climatic and environmental conditions, rather than by physiography or cultural factors.